Los hábitos de estudio y su repercusión en el rendimiento académico en estudiantes de octavo año. - Antamba, Doris V. (2022)
The purpose of this research is to determine the impact of study habits on academic performance in eighth year students of Basic General Education of the "Jacinto Collahuazo" Educational Unit, since it can be seen that the performance of the students has been seen affected by different personal and social factors that influence the main deterioration of educational quality, bad study habits generate problems in educational performance. The study was developed following a quantitative, descriptive approach, the sample consisted of 45, applying a survey of 36 questions as a data collection instrument, digital tools such as Microsoft Excel and SPSS statistical software were used, which performed the analysis. of the survey data, obtaining favorable results using statistical indicators of reliability of a measurement scale such as Cronbach's alpha and Rho Spearman. With reference to the results, it is interpreted that there is a relationship between study habits and academic performance. In this sense, good study habits help to perform better, together with learning strategies improving academic performance, therefore, it is positively related. In conclusion, according to the data obtained in the research, students do not have good study habits due to external factors that decrease performance such as in the social and family context, on the other hand it is reflected in the lack of organization, planning and control in their school activities.